2019
DOI: 10.1038/s41467-019-10873-y
|View full text |Cite
|
Sign up to set email alerts
|

Upper tract urothelial carcinoma has a luminal-papillary T-cell depleted contexture and activated FGFR3 signaling

Abstract: Upper tract urothelial carcinoma (UTUC) is characterized by a distinctly aggressive clinical phenotype. To define the biological features driving this phenotype, we performed an integrated analysis of whole-exome and RNA sequencing of UTUC. Here we report several key insights from our molecular dissection of this disease: 1) Most UTUCs are luminal-papillary; 2) UTUC has a T-cell depleted immune contexture; 3) High FGFR3 expression is enriched in UTUC and correlates with its T-cell depleted immune microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
167
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(188 citation statements)
references
References 47 publications
18
167
2
1
Order By: Relevance
“…1b) 16 . These data are consistent with those of Robinson et al 5 and suggest that the luminal-papillary sub-type is enriched in UTUC as compared to bladder cancer where only 24% of tumors were luminal-papillary sub-type 16 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1b) 16 . These data are consistent with those of Robinson et al 5 and suggest that the luminal-papillary sub-type is enriched in UTUC as compared to bladder cancer where only 24% of tumors were luminal-papillary sub-type 16 .…”
Section: Discussionsupporting
confidence: 92%
“…Recent genomic analyses of UTUC [2][3][4][5] have identified a high incidence of potentially actionable genomic alterations including recurrent activating mutations in receptor tyrosine kinases (FGFR3, ERBB2), HRAS, PIK3CA and TSC1. These molecular profiling studies have also, however, identified significant genetic diversity among UTUC patients and a large number of genomic variants of unknown significance 6,7 .…”
mentioning
confidence: 99%
“…We identi ed FGFRs gene alteration in 26.85% of UC patients, which was close to the corresponding ratio in the TCGA database [4]. Though may have an increased sensitivity to FGFR inhibitor, UC patients with FGFRs alterations may have a lower response rate to the ICIs therapy because of the suppressed in ltration of tumor immune cells in the tumor environment [11,12]. Meanwhile, alterations in ERBB pathway, especially in ERBB2, raised increasing interest in UC recently, as 12.4% and 11% UCB patients had ERBB2 overexpressing (as tested by HER2 immunohistochemistry (IHC) staining) and mutations, respectively [13].…”
Section: Discussionsupporting
confidence: 54%
“…The poorer outcomes of this cohort of patients speak to an unmet need for unique, upper tract-specific therapeutic strategies with good scientific rationale. Robinson et al undertook comprehensive genomic and transcriptomic analysis of 37 upper tract urothelial primary tumours in an attempt to define their key biological differences from urothelial carcinoma of the bladder 12. Among the discoveries made were upregulation of FGFR3 , a T-cell-depleted immune milieu, and a luminal-papillary signature in the majority of tumours 12.…”
Section: Molecularly Matched Treatment: Targeting Driver Mutationsmentioning
confidence: 99%